Changes of Paradigm in Private International Law of Contracts – A high-level comparison between 1989 and 2024, with tribute to the Unidroit Principles, the development of arbitration law and to Simplified Global Contracting - Brödermann, Eckart (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The article on German private law of contracts compares the state of private international law in Germany in 1989 with its state today, in 2024. It demonstrates a change of paradigm by looking at six selected parameters of relevance: (i) the respect of constitutional rights and European fundamental freedoms, (ii) the unitarian European character of private international law of contracts, subject to treaties, (iii) the dissemination of the CISG, (iv) the emergence of the the Unidroit Principles as a sound system of general principles and rules of international commercial contracts, (v) the development of international arbitration, and (vi) the emergence of internet and data platform based comparative legal research. Regarding the traditional private international law of contracts, as applied by European courts (of member states of the European Union), the author observes that more European uniformity has come at the cost of complexity. At the same time, the emergence and dissemination of the Unidroit Principles – described as “the biggest achievement of the international legal society since the year 534” – has enabled Simplified Global Contracting (i.e. the choice of the Unidroit Principles in combination with an arbitration clause) and thereby more freedom on a global level.